Investigative Study on Self-Concept of Diabetes Mellitus Ulcer Patients - Istianna Nurhidayati; Marwanti Marwanti; Susminingsih Susminingsih; Sutaryono Sutaryono (Urecol Journal. Part D: Applied Sciences, 2021)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormal insulin secretion. Uncontrolled hyperglycemia condition can cause complications in the foot neuropathy and ulcers are often associated with diabetes. Diabetic ulcers have an impact on loss of bodily function, decreased activity tolerance resulting in disruption to the individual's self-concept. The aim of this study was to analized relationship between diabetic ulcers and self-concept of diabetes mellitus patients in RSUP dr. Soeradji Tirtonegoro Klaten. The study design used case control with non-probability, sampling technique was consesecutived sampling. The number of samples used were 82 samples divided into two groups: 41 controls 41 cases. analysis of the results using bivariate test with Chi-Squere. Comparative test results with Chi-Squere between DM ulcers with self-concept in the control group and case group were adjusted p value = 0.034 (OR = 0.35). Conclusion there was a relationship between diabetic ulcers with the self-concept of diabetes mellitus patients at RSUP dr. Soeradji Tirtonegoro Klaten. Based on these findings, the proposed interventions that could be implemented was to increase self concept patient with diabetic ulcer.